Student engagement with teacher oral feedback in EFL university classrooms - Wang, Bo; Yu, Shulin; Zheng, Yao; Teo, Timothy (Language teaching research : LTR, 2025)
While previous research has investigated teacher oral feedback practices and their influences on student learning, little research has examined how students interpret and engage with teacher feedback, which is critical to the feedback effectiveness and the success of learning and performance. According to Ellis, student engagement is clearly defined as the ways that students respond to the feedback, which can be cognitive, behavioral, and affective. Drawing upon students’ oral presentations together with teacher oral feedback, semi-structured interviews, stimulated recalls, reflective accounts, and PowerPoint (PPT) slides for the oral presentations, this case study investigates three undergraduates’ cognitive, behavioral, and affective engagement with teachers’ oral feedback provided on in-class oral presentations in an English as a foreign language context. The findings indicated that cognitively, the students occasionally ignored teacher feedback, but they were able to notice and understand most of the teacher feedback by using cognitive operations. Behaviorally, the students attempted to respond to teacher feedback by repairing linguistic errors, revising and editing their PPT slides, or improving their presentation delivery. Affectively, students displayed mostly positive attitudes toward teacher feedback and a wide range of discrete emotions were induced by the feedback, which were subject to students’ self-regulation. Further insights can be drawn from the findings into understanding how teachers of English as a foreign language (EFL) can help students harvest benefits when engaging with teacher oral feedback.